Protective Effect ofEthanolic Extract ofArgyreia Nervosa Leaves on Chronic-Diabetes Induced Testicular Alterations: Pharmaceutical Science-Medical science - Arunagiri, Saranya; Srinivasan; Maheshwari (International Journal of Life Science and Pharma Research, 2022)
Our objective is to evaluated the role of primary phytochemical constituents present in ethanol extracts of Argyreia nervosa, resulting in chronic diabetic males induced infertility. The current study aims to assess the protective role of ethanol extract of Argyreia Nervosa against Streptozotocin (STZ)caused alterations in blood glucose level and histopathology architectureof the testis. Phytochemical profiling of ethanolicextractArgyreiaNervosa was carried out. The diabetic model was created by giving animals 40 mg/kg/BW of STZ(intraperitoneally). Further, Argyreia nervosa was administered orally after the induction of STZ and confirmed blood glucose levels in experimental subjects. The drug dosage was (200,400 mg/kg/BW) daily for 60 days. Histopathological analysis of the removed testis at specified intervals was carried out. Ethanol extracts contain more phytochemical constituents such as tannins, phenolics, quercetin, saponins, flavonoids, beta carotene, etc. The components have more antioxidant properties when compared with methanol and petroleum ether extract. The results showed that blood glucose levels significantly decreased and noted elevated serum testosterone levels in Argyreia nervosa(400mg/kg) treated groups compared with the untreated Streptozotocin (STZ) induced group. The histopathological study revealed that the Argyreia nervosa (200&400 mg/kg/BW) treated groups show significant changes in testis when compared with the STZ induced diabetic groups. This herbal has many antioxidants, anti-diabetic, anti-microbial, antifungal, and aphrodisiac. Ethanol extract of Argyreia nervosa lowers the blood glucose level in hyperglycemic patients due to its anti-diabetic property and aphrodisiac properties. Like an adaptogenic aphrodisiac, Argyreia nervosa extracts contain potent antioxidants, which enhance sperm density and sperm quality and minimize the damage to sperm cells by scavenging free radicals resulting from excessive oxidative damage.